A rough version of that day - Wolf, Ursula; Rosa Helena (Estudios de Filosofía, 1995)
The aim is to determine issues which pertain to philosophy and literature on the basis, firstly of a common context, namely totality and secondly to outline two perspectives, such as the matter of the relationship between philosophy and literature with totality and the ethical and moral relevance of the foresaid relationship. Totality should be understood in three manners: reality and the world; the relations between men and the world and its understanding; and individual life. These variations of the concept are extended by Peter Handke and presented as discursive support by Ursula Wolf.